Suppression of Flow-Induced Noise of a Canister Vacuum Cleaner - Teoh, Choe-Yung; Lim, Jun; Abdul Hamid, Muhammad Najib; Ooi, Lu Ean; Tan, Wei Hong (International Journal of Integrated Engineering, 2023)
This paper describes the modification of a canister vacuum cleaner to reduce flow-induced noise. This research aims to identify the noise source and suppress the noise level of a canister vacuum cleaner experimentally without affecting its suction power significantly. Based on the preliminary results, the noise was mainly contributed by blade passing noise generated by the motor and airborne noise from aerodynamics origin. The blade passing frequency of the motor is 2475 Hz, while the dominant airborne noise occurs at 600 Hz. Two noise reduction methods were introduced: porous expanded polypropylene sound panels and a honeycomb noise filter in a canister vacuum cleaner. A layer of K-flex K-FONIK open-cell applied to the inner wall of the vacuum cleaner showed a 3.7 dB(A) reduction in noise level. In comparison, the honeycomb noise filter reduced the noise level by 3.4 dB(A). When both methods were implemented concurrently, the overall noise level was successfully reduced from 73.2 dB(A) to 65.8 dB(A), achieving a total reduction of 7.4 dB(A). The vacuum cleaner’s suction power was tested after the modifications, and the results showed only a 0.001 Watts or 0.93% reduction in suction power.